1976
DOI: 10.1098/rstb.1976.0038
|View full text |Cite
|
Sign up to set email alerts
|

The structure and function of thoracic exopodites in the larvae of the lobster Homarus gammarus (L.)

Abstract: The first three larval stages of the lobster Homarus gammarus are pelagic swimming animals. A description is given of the exopodite apparatus of the thoracic appendages that provide lift and propulsive power in these stages. Setal arrangement and display provides greater surface area during power strokes. Musculature is peculiar to the exopodites and concerned with rotational movements of the appendage. Metachronal beating takes place with the segmental appendages moving in a variable sequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 25 publications
(23 reference statements)
1
2
0
Order By: Relevance
“…Accordingly, the experimental light must have been well discernible by the lobster larvae. Under laboratory conditions newly hatched larvae always stayed at the surface and swam directly towards any light source in accordance with observations of Neil et al (1976), Dunn & Shelton (1983) and Watt & Arthur (1996), who reported that larvae after hatching always swim towards the sea surface. In our experiments, the newly hatched lobster larvae reacted immediately to light Á irrespective of the direction Á even if it came from the bottom and responded with a downward vertical swimming speed of about 4Á5 cm s (1 (including the sinking rate of 1.7 cm s (1 ).…”
Section: Phototaxis and Vertical Distributionsupporting
confidence: 89%
See 1 more Smart Citation
“…Accordingly, the experimental light must have been well discernible by the lobster larvae. Under laboratory conditions newly hatched larvae always stayed at the surface and swam directly towards any light source in accordance with observations of Neil et al (1976), Dunn & Shelton (1983) and Watt & Arthur (1996), who reported that larvae after hatching always swim towards the sea surface. In our experiments, the newly hatched lobster larvae reacted immediately to light Á irrespective of the direction Á even if it came from the bottom and responded with a downward vertical swimming speed of about 4Á5 cm s (1 (including the sinking rate of 1.7 cm s (1 ).…”
Section: Phototaxis and Vertical Distributionsupporting
confidence: 89%
“…The locomotion ability of larvae changes during their larval development (Ennis 1995) and the major swimming appendages of the pelagic larvae are the exopodite branches of the third maxillipeds, the chelipeds and the four pairs of pereipods (Neil et al 1976). By beating of the exopodites, the larvae carry forward, backwards or upwards; when their motion ceases, however, the larvae sink towards the bottom (Hadley 1908).…”
Section: Stocks Of European Lobsters (Homarus Gammarusmentioning
confidence: 99%
“…Before going on to discuss the determinative influences, it is interesting to note that the critical period is also the time when the lobster changes its habitat. The larval stages are all pelagic and live in the plankton, staying afloat by accessory swimming appendages ( Neil, Macmillan, and Laverack, 1976). These accessory appendages degenerate at the molt to the fourth stage (Govind, Kirk, and Pearce, 1988a).…”
Section: Critical Period For Determining Asymmetrymentioning
confidence: 99%